METODE PENETAPAN MAQOSHID AL SYARI'AH: Studi Pemikiran Abu Ishaq al Syatibi - Aziz, Muhammad; Sholikah, Sholikah (ULUL ALBAB Jurnal Studi Islam, 2013)
The spirit and core of each something that is prescribed by Islam, is basically between humans and bring benefit to prevent danger to him. Thus, it is important to note that in addition to undergoing the whole law of God entrusted to his servant, there are also others, is to know the ins and outs of determining the intent and purpose of the pensyariatan a particular law. In this study, before determining how to define maqashid Islamic better writer would also browse and find out how to convey maqashid sharia (thuruq al ma'rifah li maqashid al Sharia), which by the way; research on the particulars of the Quran al Sunnah and al Ijma, in addition, specific temporal aspects, the approach can be based on the proposition logic (aqli) and optimization of the use of reason and the correct ratio through a series of experiments, the empirical habit, a collection of hypotheses. Abu Ishaq Ibrahim al Syathibi is among so many scholars' are very well known in this field of study. According to him, how to set maqashid al sharia: 1) Mujarrad al amr wa al nahy al ibtida'i at tasrihi, 2) Illat consider the context of each command and prohibition, 3) Nothing all maqashid derivatives (at tabi'ah), 4) The absence of information Sharai (sukut al syar'i).